Strain, strain rate, and mechanical power: An optimization comparison for oscillatory ventilation. (6th August 2019) - Herrmann, Jacob; Tawhai, Merryn H.; Kaczka, David W.
Abstract: The purpose of this study was to assess the potential for optimization of mechanical ventilator waveforms using multiple frequencies of oscillatory flow delivered simultaneously to minimize the risk of ventilator‐induced lung injury (VILI) associated with regional strain, strain rate, and mechanical power. Optimization was performed using simulations of distributed oscillatory flow and gas transport in a computational model of anatomically derived branching airway segments and viscoelastic terminal acini under healthy and injured conditions. Objective functions defined by regional strain or strain rate were minimized by single‐frequency ventilation waveforms using the highest or lowest frequencies available, respectively. However, a mechanical power objective function was minimized by a combination of multiple frequencies delivered simultaneously. This simulation study thus demonstrates the potential for multifrequency oscillatory ventilation to reduce regional mechanical power in comparison to single‐frequency ventilation, and thereby reduce the risk of VILI. Abstract : A computational model of distributed oscillatory flow and gas transport was used to assess the potential for optimization of mechanical ventilator waveforms using multiple frequencies of oscillatory flow delivered simultaneously. The risks of ventilator‐induced lung injury associated with regional strain or strain rate were minimized by single‐frequency ventilation waveforms using the highest or lowest frequencies available, respectively. However, injury associated with mechanical power was minimized by a combination of multiple frequencies delivered simultaneously, or multifrequency oscillatory ventilation.